Trocas gasosas e metabolismo antioxidativo em plantas de girassol em resposta ao déficit hídrico - Carneiro, Marília Mércia Lima Carvalho (2011)
This study aimed evaluates parameters related to photosynthesis and antioxidant metabolism in two sunflower cultivars under different water regimes in the initial growth phase. Seeds of the cultivars MG2 and M735 were grown in pots with a capacity of 10 L, using soil as substrate. Thirty days after sowing was done a thinned to four plants per pot, watered daily. Two months after the treatments were established, where a portion of the plants of each cultivar was kept watered daily (control) and another submitted to the full suspension of irrigation (water deficit). After 24 hours, five and twelve days of induction treatment in predawn leaf water potential was measured and leaf chlorophyll content in the early hours. Between 9:00 and 10:00 hours were measured photosynthetic parameters and chlorophyll fluorescence. Then, leaves and roots were collected and stored in a freezer at -80°C for quantification of cell damage and antioxidant enzymes. In response to water stress imposed at the end ofof the evaluations , there was a sharp drop in water potential of both cultivars . On the other hand, the chlorophyll index was down only in cv M735. The decline in leaf water potential reflected in reductions in stomatal conductance, transpiration rate, net assimilation of CO2 and its internal concentration in both cultivars, emphasizing greater reductions in transpiration and internal CO2 concentration, hence increasing efficiency water use for both varieties. The fluorescence of chlorophyll a decreased effective quantum yield photochemistry (FV '/ FM') and produce effective quantum of photosystem II (ΦPS2) in cv MG2. During that same period we observed an increase in the levels of lipid peroxidation, H2O2 content and activity of SOD and CAT, with the greatest difference compared to control, especially in cv M735, which prevented more effectively oxidative stress.